Previous education experience impacts student expectation and initial experience of transitioning into higher education - Timmis, Matthew A.; Hibbs, Angela; Polman, Remco; Hayman, Rick; Stephens, David (Frontiers in Education, 2024)
IntroductionEntering higher education (HE) is one of the most significant transitions in a student’s life and is negatively impacted by any disparity between expectation and initial experience when joining their course.MethodThe current study explored how the students’ experiences of learning and teaching practices in their previous educational environment influenced their expectations and initial experiences of HE. The study adopted a mixed methods approach, initially surveying 69 students concerning their previous educational experiences, expectations and experiences of HE. Informed by the questions in the survey, two semi-structured focus groups comprising a total of 6 students were completed and analysed using inductive thematic analysis.Results and discussionThe current research identified specific challenges students face as they transition into HE, often resulting in an initial culture shock as that adapt to their new learning environment. These challenges are, to some extent, a consequence of their previous learning environment. Whilst expectations of HE were cultivated in their previous educational environment, they were not always accurate and resulted in a mismatch between expectation and reality of HE. This article identifies what may be missing for a student as they transition from further education into HE, and explores some of the opportunities HE faces in addressing these deficits.